A protocol for management of blood loss in surgical treatment of peritoneal malignancy by cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Issue 2 (31st March 2016) - Sargant, N.; Roy, A.; Simpson, S.; Chandrakumaran, K.; Alves, S.; Coakes, J.; Bell, J.; Knight, J.; Wilson, P.; Mohamed, F.; Cecil, T.; Moran, B.
SUMMARY: Background and aims: The treatment of peritoneal malignancies with cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to be associated with massive surgical blood loss. Maintaining high fibrinogen levels throughout surgery may reduce blood loss in these patients. The primary aim of the study was to see if Tranexamic Acid (TXA) and cryoprecipitate reduced surgical blood loss and hence red cell transfusions. A comparison was made with a cohort of patients treated with fresh frozen plasma (FFP) alone. The secondary aim was to measure the effect of both protocols on coagulation parameters and the incidence of arterial or venous thrombosis. Method: We used prospectively collected data from 201 patients who had complete CRS with HIPEC for peritoneal malignancy using different protocols during two discrete 12‐month time periods. Results: The new transfusion protocol led to a higher average fibrinogen level intra‐operatively and post‐operatively, with a significant reduction in average RBC, FFP and platelet transfusion intra‐operatively per patient from 4·2 to 1·8 units, 6·2 to 0·2 units and 0·1 to 0 units, respectively. No significant difference in PT or APTT was seen between patients treated with the standard and new protocols. Venous thrombosis occurred in seven patients treated with the standard protocol and five with the new protocol. A single case of arterial thrombosis was seen in both groups. Conclusion: Patients treated with upfront TXA and cryoprecipitate during CRS required less RBC transfusion than those treated with the standard protocol of early FFP.